(untitled) (Revista de Ciências Agroveterinárias, 2022)
The presence of antimicrobial residues in informal milk, sold in inland cities, a situation commonly found in Brazilian cities, since the inspection of this type of product is incipient. As a case study, the municipalities of Arcos, Lagoa da Prata and Santo Antônio do Monte, in the center-west of Minas Gerais, were considered. Two collections were carried out in 22 informal sales points in 2020. To detect antimicrobial residues, the Trisensor® test was used, in which the presence of three groups of antimicrobials can be observed: beta-lactams, tetracyclines and sulfonamides. After performing the analyses, negative results were observed for the groups of tetracyclines and sulfonamides. However, when evaluating the beta-lactam group, positive results were observed: in a total of 44 samples, 54.5% were positive for the presence of beta-lactams (24 samples). The high incidence of antimicrobial residues in the analyzed samples (54.5%) confirms the need for surveillance of the product that is commercialized, and it is extremely important to adopt strict measures by inspection bodies since the presence of residues of antimicrobials in raw milk can, directly and indirectly, affect health.